Identification of Diverse Integron and Plasmid Structures Carrying a Novel Carbapenemase Among Pseudomonas Species - Liapis, Eleni; Bour, Maxime; Triponney, Pauline; Jové, Thomas; Zahar, Jean-Ralph; Valot, Benoît; Jeannot, Katy; Plésiat, Patrick (Frontiers in Microbiology, 2019)
A novel carbapenem-hydrolyzing beta-lactamase, called IMP-63, was identified in three clonally-distinct strains of Pseudomonas aeruginosa and two strains of Pseudomonas putida isolated within a four year timeframe in three French hospitals. The blaIMP-63 gene that encodes this carbapenemase turned out to be located in the variable region of four integrons (In1297, In1574, In1573 and In1572) and to coexist with novel or rare gene cassettes (fosM, gcu170, gcuF1) and insertion elements (ISPsp7v, ISPa16v). All these integrons except one (In1574) were flanked by a copy of insertion sequence ISPa17 next to the orf6 putative gene, and were carried by nonconjugative plasmids (pNECK1, pROUSS1, pROUSS2, pROUE1). These plasmids exhibit unique modular structures and partial sequence homologies with plasmids previously identified in various non-fermenting environmental Gram-negative species. Lines of evidence suggest that ISPa17 promoted en bloc the transposition of IMP-63-encoding integrons on these different plasmids. As demonstrated by genotyping experiments, isolates of P. aeruginosa harboring the 28.9-kb plasmid pNECK1 and belonging to international “high-risk” clone ST308 were responsible for an outbreak in one hospital. Collectively, these data provide an insight into the complex and unpredictable routes of diffusion of some resistance determinants, here blaIMP-63, among Pseudomonas species.